PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV A SDN 161 PEKANBARU - Viky Mulyati; Eddy Noviana; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve students learning outcomes in civic studies for grade IV A SDN 161 Pekanbaru, through the application of cooperative learning models of talking stick. The method used in this research is Classroom Action Research (CAR). Subject in this study were students as much as of grade IV A SDN 161 Pekanbaru in academic year of 2015/2016. And the number of students as 35 people. Instrument used in thisresearch are observational sheet and test in the last cycle. This research was conducted in two cycle. From the analysis of the data the researched found that there is an improvement in student learning outcomes. This increase is evident from the results of student learning before using model talking stick is 68,85 square on the second cycle increased a 79,28. On the basic value there was only 16 (54,28%) students who achieve the learning mastery . in the first cycle, the student who achieve the learning mastery were increased. It was about 14,29% from the basic value, it rached 21 (60%) students . On the second cycle the student who achieve the learning mastery were increased about 30 (25,71%) from the first cycle., become 85,71%. The same thing also happened to the students learning activities. In the first cycle, students learning activities is 68,75% and on the second cycle, students learning activities were increased about 18,75%from the first cycle, become 87,50%. Based on the analysis of data of this study it can be concluded that the use og Talking Stick in Cooperative Learning Model can improve students learning outcomes and learning activities for grade student of IV A SDN 161 Pekanbaru.